2021
DOI: 10.1039/d1cp03495b
|View full text |Cite
|
Sign up to set email alerts
|

Dissociative photodetachment of H3O2: a full-dimensional quantum dynamics study

Abstract: The transition state is a central concept of chemistry. Photoelectron-photofragment coincidence (PPC) spectroscopy has been proven as an attractive method to study the transition state dynamics. Within a state-of-the-art full-dimensional...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…With one water molecule attached, the OH − (H 2 O) cluster has a spectrum with at least two vibrational progressions that are assigned to the proton asymmetric stretching mode and its coupling with the proton bending and the O─O symmetric stretching modes, respectively, identified by combining the NIPES measurements with a four-dimensional Franck-Condon simulation (23). This assignment is further supported by a full-dimensional quantum chemical study (25).…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…With one water molecule attached, the OH − (H 2 O) cluster has a spectrum with at least two vibrational progressions that are assigned to the proton asymmetric stretching mode and its coupling with the proton bending and the O─O symmetric stretching modes, respectively, identified by combining the NIPES measurements with a four-dimensional Franck-Condon simulation (23). This assignment is further supported by a full-dimensional quantum chemical study (25).…”
Section: Resultsmentioning
confidence: 77%
“…Unexpectedly, after almost two decades from the previous IR study, no photoelectron spectrum has been reported for OH − (H 2 O) n clusters, except for the binary OH − (H 2 O) complex (21)(22)(23). Current advances in cryogenic techniques have resulted in improved spectral resolution (23), further establishing the importance of the method as a benchmark for high-level quantum dynamics simulations, such as the ones reported for OH − (H 2 O) (24,25). Although less sensitive in probing molecular vibrations, photoelectron spectroscopy is also capable of yielding the electron binding energies (EBEs).…”
Section: Introductionmentioning
confidence: 99%
“…Here is the Bohr radius. Within this constraint, the full-dimensional Hamiltonian is reduced to a seven-dimensional one that can be written as ( hereafter) 49 : where R , r 1 , r 2 , and r 3 are defined as the distance between centers of mass of H A F B and H C H D N E , the interatomic distance of H A F B , the distance from H C to the center of mass of H D N E , and the interatomic distance of H D N E , respectively, and the corresponding reduced masses are denoted by , , , and . is the rotational angular momentum operator of H A F B , is the orbital angular momentum operator along r 2 , and is the rotational angular momentum operator of H D N E .…”
Section: Methodsmentioning
confidence: 99%